Increased plasma TACE activity in subjects with mild cognitive impairment and patients with Alzheimer's disease - Sun, Qiying; Hampel, Harald; Blennow, Kaj; Lista, Simone; Levey, Allan; Tang, Beisha; Li, Rena; Shen, Yong (Journal of Alzheimer's disease, 2014)
Evidence suggests that the tumor necrosis factor receptor (TNFR)-signaling pathway contributes to the pathogenesis of Alzheimer's disease (AD). TNF-α converting enzyme (TACE/ADAM-17) can cleave both pro-TNF-α and TNF receptors. Recently, we have shown that TACE activity in the cerebrospinal fluid (CSF) of subjects with mild cognitive impairment (MCI) and AD patients is significantly higher than that of cognitively healthy controls (HC). To date, it is not clear whether TACE activity could be detected in the human plasma and whether TACE activity in MCI and AD patients is different from that in HC. We analyzed TACE expression and activity in a large clinical sample of 64 patients with AD, 88 subjects with MCI, and 50 age-matched HC recruited from two distinct academic centers. Plasma TACE protein levels did not differ significantly in the three study groups (AD, MCI, and HC). However, plasma TACE activity in subjects with MCI and AD patients was significantly higher than that in HC. Moreover, in MCI and AD groups, we found a significant correlation between plasma TACE activity and CSF t-tau and Aβ42 levels and CSF Aβ42/tau ratios. In AD patients, the levels of plasma TACE activity correlated significantly and negatively with cognition. These findings further support the role of the TNF-α receptor complex in AD-related neuroinflammation and propose TACE plasma activity as a promising hypothesis-driven biomarker candidate for detection, diagnosis, and prognosis of prodromal and clinical AD.